(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Pediatric ophthalmology remains one of the most important issues in modern medicine, as vision impairment at an early age can affect a child’s cognitive development and social adaptation. According to the World Health Organization, more than 1.4 million children worldwide suffer from irreversible blindness, and over 19 million have varying degrees of vision impairment . Research show that the leading causes of blindness and visual impairment in children remain retinopathy of prematurity, congenital cataracts, juvenile glaucoma, hereditary retinal dystrophies, progressive forms of myopia, and eye injuries . However, the structure of diseases varies significantly: in developed countries, myopia is the most prevalent, while in developing regions, retinopathy of prematurity and congenital cataracts remain significant . Particular attention is paid to the development of region-specific prevention programs and the implementation and effective use of measures to reduce the global burden of childhood blindness.